Persistence of a network core in the time evolution of interlocking directorates - Mishael Milaković; Matthias Raddant; Laura Birg (Kiel University, Department of Economics, 2009)
We examine the bipartite graphs of German corporate boards in 1993, 1999 and 2005, and identify cores of directors who are highly central in the entire network while being densely connected among themselves. Germany's corporate governance has experienced significant changes during this time, and there is substantial turnover in the identity of core members, yet we observe the persistent presence of a network core, which is even robust to changes in the tail distribution of multiple board memberships. Anecdotal evidence suggests that core persistence originates from the board appointment decisions of largely capitalized corporations.
Keywords: 330; Network core; density; centrality; interlocking directorates; corporate governance; Vorstand; Soziales Netzwerk; Wirtschaftskonzentration; Graphentheorie; Deutschland